Optimal picocell base station density for energy-efficient heterogeneous cellular network under received power constraint. (1st May 2020) - Yang, Jie; Pan, Ziyu; Hu, Han
Heterogeneous cellular networks (HCNs) have emerged as the primary solution for overwhelming traffic demands. However, the dense deployment of small cell base stations (BSs) inevitably triggers a tremendous escalation of energy consumption. In this paper, we apply tools from stochastic geometry to investigate and optimise the energy efficiency (EE) for a two-tier HCN. The average successful transmission rate per unit area of a two-tier HCN is derived, and then the total power consumption of all the BSs in per unit area of a two-tier HCN is derived. Based on that, the EE expression of the whole HCN is formulated. We analysis the received signal power constraint for a typical user and convert the power constraint to density constraint. Finally, we use a one-dimensional optimisation algorithm to maximise the EE by optimising picocell BS density. Simulation results validate the accuracy of the theoretical analysis and demonstrate the proposed optimal picocell BS density can obviously improve EE.